2018
DOI: 10.17582/journal.aavs/2018/6.10.443.460
|View full text |Cite
|
Sign up to set email alerts
|

Citrus limon and Paradisi Fruit Peel Hydroethanolic Extracts Prevent the Progress of Complete Freund’s Adjuvant-Induced Arthritis in Male Wistar Rats

Abstract: | This study was designed to assess the preventive effect of Citrus limon (C. lemon) and Citrus paradisi (C. paradisi) fruit peel hydroethanolic extracts on the progress of complete Freund's Adjuvant (CFA)-induced arthritis in male Wistar rats. Rheumatoid arthritis rat model was established by subcutaneous injection of 0.2 ml CFA into the right hind paw of each rat at two successive days. Arthritic rats were administered C.limon and C. paradisi fruit peel hydroethanolic extracts by oral gavage of 100 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…IL-17 has the potential to cause matrix damage and in ammation in OA patients [52]. The present results are also in accordance with Ahmed et al [9], Saber et al [51], Ahmed et al [53], Ahmed et al [54], and Zhang et al [55] who reported a signi cant drop in IL-4 expression in arthritic rats in relation to normal control.…”
Section: Discussionsupporting
confidence: 91%
“…IL-17 has the potential to cause matrix damage and in ammation in OA patients [52]. The present results are also in accordance with Ahmed et al [9], Saber et al [51], Ahmed et al [53], Ahmed et al [54], and Zhang et al [55] who reported a signi cant drop in IL-4 expression in arthritic rats in relation to normal control.…”
Section: Discussionsupporting
confidence: 91%
“…The primer sequences for β -actin mRNA are as follows: forward: 5′TCACCCTGAAGTACCCCATGGAG3′ and reverse: 5′TTGGCCTTGGGGTTCAGGGGG3′. All the primers used in this experiment were synthesized by Sangon Biotech (Shanghai, China) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 125 ] The various studies presented the therapeutic value of ethyl alcohol and methyl alcohol extract using plant bark part for treatment of RA at different doses orally administered against collagen type‐II‐induced arthritic mice, resulting in reducing free radical generation by lymphocytes along with inhibiting TNF‐α, CAII and all proteins involved in RA. [ 126,127 ] Citrus limon – The Citrus Limon commonly known as lemon belongs to Rutaceae family. The lemon peel extract comprises of bioactive compounds like pyrogallic acid, caffeic acid, eugenol and quercetin and when used at various doses suppresses the inflammation, and the usage of leaf extract of C. limon as therapy against Freund’s adjuvant arthritic model tends to reduce free radical level and acts as antioxidant by inhibition of xanthine oxidation.…”
Section: The Various Herbal Plants Used In the Treatment Of Rheumatoimentioning
confidence: 99%